The Contribution of the Scene to Latin American Media Landscape - García González, Daniel (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2013)
We have a look at how the jailbreak community has influenced over Apple Tv device's multimedia streaming offer to consumers paying special attention on those contents in Spanish and Portuguese. The company from Cupertino has always mantained tight restrictions on which contents can be streamed through this player, but independent developers have made an effort to break these barriers and push the device to its limits. They have open a great field of opportunities for contents streaming over this device, such as the popular platforms XBMC or Boxee. Even though, Spanish spoken users can also find a significant amount of digital television channels streaming directly onto their devices thanks to the individu-al efforts of specific IT technicians' initiative.